PROMOTION STRATEGY AND BRAND LOYALTY: A STUDY OF MOBILE PAYMENT IN SOUTH SULAWESI - Nurqamar, Insany Fitri (Hasanuddin Economics and Business Review, 2021)
Fintech or Financial Technology is an innovation that comes from digitizing management in the financial sector. Fintech is popularly used by millennials as a cash payment replacement tool. The purposes of this research are to determine and analyze the effect of promotional strategies used on brand loyalty. The respondents of this research were 140 millennial's mobile payment users, specifically OVO, LinkAja, and Gopay which were randomly selected by using the proportional random sampling method. The data collection techniques used literature study and field study. It will be analyzed by using multiple regression methods. The results of the research have demonstrated that the promotion strategy affects positively and significantly toward brand loyalty of mobile payment OVO, Gopay, and LinkAja.